(3GdEaMGe dGaFOI GdHGWfjI GdYXGe aj GdQO Ydjge aj GdCSQGQ GdEdgjI hGdeHGMK GdcdGejIs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPi edCJ bdhH GdYGQajf CfhGQ YXeJg CeG HYO aMb Ydi ef jJSe ai Yde GdcdGe PQhI GdSfGe Gf jchf Cge TF YfOg GdOaGY Yf MhRI GdOjf s
(3BNQgG (B:s
(3hCMQR dfG ehGWf GdXaQ hGNPd YOhfG YeG jMGhd hdG jXaQ Je cJGH GdEaMGe s
(3HgG fXGe GdJYbjHIs
(3hgh ai GdQO Ydjge ai GdGSQGQ GdEdgjI hGdeHGMK GdcdGejI HdZJ bQCJg hebGHdJgs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B143s
Keywords: (3eJaQbGJs